IMPLEMTASI MEDIA AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN HASIL BELAJAR SISWA - Zubaidi, Ahmad; Eva Diadara; Muvidah; Yuli Hafsari (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The presence of technology in various aspects of human life has had a significant impact on the world of education. Teachers, in the teaching process, are indirectly required to develop media and learning strategies that are not just monotonous in the form of lectures or discussions. They must keep up with technological developments and integrate them into the learning process. The implementation of audiovisual media is part of the teachers' and educators' efforts to increase students' motivation and learning outcomes. This research uses qualitative methods with a descriptive approach, including stages such as literature review, observation, interviews, data analysis, and drawing conclusions. Based on the research results, the use of audiovisual media is very effective in improving the quality of learning and students' motivation in Islamic Religious Education at MTs Az-Zainiya I Paiton Probolinggo. Audiovisual media not only helps students understand the material better but also makes learning more interesting and enjoyable. Teachers are expected to continue developing and utilizing this media in the learning process as an effort to improve services to students. This research also emphasizes the importance of innovation in teaching methods to enhance the quality of education and students' learning motivation.